Enhancement of energy conversion and emission reduction of Calophyllum inophyllum biodiesel in diesel engine using reactivity controlled compression ignition strategy and TOPSIS optimization. (1st February 2023) - Tamilvanan, A.; Mohanraj, T.; Ashok, B.; Santhoshkumar, A.
Abstract: The present investigation mainly focuses on the abatement of NOx and soot emissions and enhancing the performance of the CI (Compression Ignition) engine through RCCI (Reactivity Controlled Compression Ignition) strategy with low reactive gasoline as an inducted fuel. The high reactive biodiesel extracted from Calophyllum inophyllum feedstock was an ignition source of RCCI combustion. Investigational results have revealed that combustion of RCCI has shown an enhancement of about 0.2–1.2%, 4.9–13.6%, and 11.3–44.6% for Brake Thermal Efficiency (BTE), maximum in-cylinder combustion pressure (Pmax ), and Net Heat Release Rate (NHRR), respectively at full load when compared to biodiesel blends. Similarly, RCCI strategy significantly reduces the emissions of NOx and soot by 24.40–43.74% and 31.28%–52.57% respectively at maximum loads. On the other hand, emissions of CO and HC are higher than the biodiesel at all loads. However, an upsurge in gasoline injection from 3 ms to 5 ms in RCCI mode decreases Pmax, NHRR, BTE, and NOx and soot emissions. This is mainly attributed to the superior cooling effect of gasoline and longer ignition delay. Multi-response optimization is performed with TOPSIS, B10 + 3 ms GF, and 100% load is identified as an optimal operating condition. Graphical abstract: Image 1 Highlights: RCCI strategy enhances diesel engine emission characteristics fuelled with CIBD. 3 ms gasoline addition in the biodiesel blends shows higher BTE than B10 and B20. Premixed and diffused combustion phasing are attained in the RCCI strategy. In-cylinder pressure and heat release rate of RCCI strategy are superior to diesel. NOx and soot emissions are lower, and CO & HC are higher than the biodiesel.